FAMILY CONFLICT MANAGEMENT: QUR’ANIC PERSPECTIVE - Munawirsazali Munawirsazali; Imam Taufiq; Misbah Zulfa Elizabeth (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2024)
This study discusses the concept of family conflicts and their management according to the perspective of the Qur'an. The literature review and thematic approach found five conflict areas in the family: leadership and husband-wife relations; the fulfilment of rights and obligations; the achievement of family vision, mission and goals; attitude and physical intimacy issues; and husband-wife incompatibility. Meanwhile, the Qur'anic family conflict management includes minimising and avoiding violence and encouraging positive behavioural changes among family members.